The Representation of American Cultural Values in Gift-Giving Practices in The Gift of the Magi - Sekar Gading; Kristin Marwinda (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2026)
This study examines the representation of gift-giving as part of American culture in O. Henry’s short story The Gift of the Magi and explores how cultural values are reflected through this practice. Gift-giving in literature is not only viewed as a material exchange but also as a symbolic expression of love, sacrifice, sincerity, and emotional connection. This research aims to identify how gift-giving is represented in the story and how American cultural values are reflected through the characters’ actions. The study uses a qualitative descriptive method and applies Stuart Hall’s theory of representation as the main theoretical framework. Data were collected from dialogues, narrative descriptions, character actions, and symbolic elements related to gift-giving. The findings show that gift-giving is represented as an emotional and symbolic act rather than an economic activity. The story highlights four main representations: love and emotional expression, sacrifice as a cultural meaning, reflections of American cultural values, and the symbolic significance of gifts beyond material usefulness. The study concludes that emotional sincerity is more important than material value. Furthermore, the story reflects American ideals such as generosity, togetherness, selflessness, and devotion, especially within Christmas traditions.